2018
DOI: 10.20882/adicciones.945
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de consumo de alcohol, tabaco y drogas ilegales en personas transexuales

Abstract: Este estudio evalúa los patrones de consumo de sustancias en personas transexuales de hombre a mujer (H-M) y de mujer a hombre (M-H). Un total de 251 personas transexuales (163 H-M y 88 M-H), atendidas en la Unidad de Identidad de Género de Cataluña, completaron un cuestionario autoadministrado sobre el consumo de alcohol, tabaco, cannabis, cocaína, opiáceos y drogas de diseño. Los resultados se compararon con datos del Servicio Nacional de Salud en población general en Cataluña (estudio EDADES 2013). La preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…This led some studies to explore intragroup differences, which indicated a higher prevalence of tobacco use among transgender men compared to transgender women [31]. Other work described the opposite, with a higher risk of tobacco and other drug use found among the group of transgender women [49]. However, still other studies pointed towards heterogeneity between the general transgender population and the cisgender men group, with an increased prevalence of tobacco use among these aforementioned groups compared to the female cisgender group [48].…”
Section: Discussionmentioning
confidence: 99%
“…This led some studies to explore intragroup differences, which indicated a higher prevalence of tobacco use among transgender men compared to transgender women [31]. Other work described the opposite, with a higher risk of tobacco and other drug use found among the group of transgender women [49]. However, still other studies pointed towards heterogeneity between the general transgender population and the cisgender men group, with an increased prevalence of tobacco use among these aforementioned groups compared to the female cisgender group [48].…”
Section: Discussionmentioning
confidence: 99%
“…Las sustancias de mayor consumo son: el alcohol, la marihuana, la cocaína y sus derivados (Reback y Fletcher, 2014). Además, las prevalencias de consumo de MT son mayores a las de población general, y hasta diez veces mayores que la de hombres trans (HT)(Gómez-Gil et al, 2019). Este consumo puede estar asociado a la búsqueda de situaciones que permitan soportar las realidades de un entorno generalmente difícil, y con el fin de reducir los efectos del alcohol(Gómez-Gil et al, 2019;Yarns et al, 2016).…”
unclassified
“…Además, las prevalencias de consumo de MT son mayores a las de población general, y hasta diez veces mayores que la de hombres trans (HT)(Gómez-Gil et al, 2019). Este consumo puede estar asociado a la búsqueda de situaciones que permitan soportar las realidades de un entorno generalmente difícil, y con el fin de reducir los efectos del alcohol(Gómez-Gil et al, 2019;Yarns et al, 2016). Entre los factores asociados, se ha encontrado como la experiencia previa de abuso sexual, aumentó casi en tres veces la posibilidad de consumir cocaína en MT de Repúbli-ADICCIONES, 2021 • VOL.…”
unclassified